(untitled) (The Journal of Knowledge and Innovation, 2024)
Travel writing generally expresses the feelings, ideas and experiences of the traveler in the form of nonfiction. However, in the modern period, many travelers began to explain history and culture of the places they visited. This paper investigates the traces of past events and customs as well as rituals of the places and people in Dhakal’s Tyo Ujyalo Karnali. This study is significant as it informs the readers about the geography of distant Karnali region and people and their culture and history by Dhakal’s traveling experience. The research is qualitative and it explores the description of rituals and narratives of Karnali region as mentioned in the text. The major objectives of the research are to infer the writer’s collection of information related to art, culture, history and people of Karnali and to expose the richness of Karnali’s civilization. The major finding of the paper is travel writing can globalize the local culture and history. Dhakal travels Karnali and discloses the social values, art, culture and history of the region. High land agriculture and natural resources makes Karnali region the land of immense possibilities. Dhakal begins a new practice in the text making travel writing a source for culture and history for the readers. The researchers can further study the text for exploring the authorial presence in it.